Drop Cost and Wavelength Optimal Two-Period Grooming with Ratio 4 - Bermond, Jean-Claude; Colbourn, Charles J.; Gionfriddo, Lucia; Quattrocchi, Gaetano; Sau, Ignasi (SIAM journal on discrete mathematics, 2010)
The authors study grooming for two-period optical networks, a variation of the traffic grooming problem for wavelength division multiplexed (WDM) ring networks introduced by Colbourn, Quattrocchi, and Syrotiuk. In the two-period grooming problem, during the first period of time there is all-to-all uniform traffic among n nodes, each request using 1/C of the bandwidth; and during the second period there is all-to-all uniform traffic only among a subset V of v nodes, each request now being allowed to use ... of the bandwidth, where ... The authors determine the minimum drop cost (minimum number of add-drop multiplexers) for any n, v and C = 4 and ... To do this, the authors use tools of graph decompositions. Indeed the two-period grooming problem corresponds to minimizing the total number of vertices in a partition of the edges of the complete graph kn into subgraphs, where each subgraph has at most C edges and where furthermore it contains at most ... edges of the complete graph on v specified vertices. (ProQuest: ... denotes formulae/symbols omitted.)